The Politics and Policies of Relief, Aid and Reconstruction - Attina, Fulvio. author. aut Link
XVI, 265 p.
Keywords: Disaster policies present a new challenge to the practitioners and students of global politics; this book explains how political science enriches the contribution of the social sciences to the study of disaster relief, aid and reconstruction following the major disaster events, both natural and man-made, of recent times.